Toward the elimination of hepatitis B: networking to promote the prevention of vertical transmission of hepatitis B virus through population-based interventions and multidisciplinary groups in Africa - Torimiro, Judith Ndongo Embola; Duri, Kerina; Goumkwa, Nadège M.; Atah, Solange M.; Ndzie Ondigui, Juliette-Laure; Lobe, Cindy; Bouyou, Marielle; Ndeboko, Bénédicte; Mahamat Moussa, Ali; Police, Camengo; Awoumou, Patrick; Peyonga, Puinta; et al. (Frontiers in Public Health, 2024)
The WHO African Region had 81 million people with chronic hepatitis B in 2019, which remains a silent killer. Hepatitis B virus (HBV), hepatitis delta virus (HDV), and HIV can be transmitted from the mother to child. If the HBV infection is acquired at infancy, it may lead to chronic hepatitis B in 90% of the cases. WHO reports that 6.4 million children under 5 years live with chronic hepatitis B infection worldwide. The prevention of mother-to-child transmission (PMTCT) of HBV is therefore critical in the global elimination strategy of viral hepatitis as we take lessons from PMTCT of HIV programs in Africa. We sought to create a network of multidisciplinary professional and civil society volunteers with the vision to promote cost-effective, country-driven initiatives to prevent the MTCT of HBV in Africa. In 2018, the Mother–Infant Cohort Hepatitis B Network (MICHep B Network) with members from Cameroon, Zimbabwe, and the United Kingdom and later from Chad, Gabon, and Central African Republic was created. The long-term objectives of the network are to organize capacity-building and networking workshops, create awareness among pregnant women, their partners, and the community, promote the operational research on MTCT of HBV, and extend the network activities to other African countries. The Network organized in Cameroon, two “Knowledge, Attitude and Practice” (KAP) surveys, one in-depth interview of 45 health care workers which revealed a high acceptability of the hepatitis B vaccine by families, two in-person workshops in 2018 and 2019, and one virtual in 2021 with over 190 participants, as well as two workshops on grant writing, bioethics, and biostatistics of 30 postgraduate students. Two HBV seroprevalence studies in pregnant women were conducted in Cameroon and Zimbabwe, in which a prevalence of 5.8% and 2.7%, respectively, was reported. The results and recommendations from the MICHep B Network activities could be implemented in countries of the MICHep B Network and beyond, with the goal of providing free birth dose vaccine against hepatitis B in Africa.